PENGARUH Return On Asset (ROA) Return On Equity (ROE) Dan Net Profit Margin (NPM) TERHADAP NILAI PERUSAHAAN: Indonesia - Kalsum Yahya; Muhammad Nur Fietroh (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2021)
This study aims to determine the effect of return on assets (ROA), return on equity (ROE), and net profit margin (NPM), on the value of study companies in on state-owned banks listed on the Indonesian stock exchange for the 2015-2019 period. The model used in data analysis is multiple linear regression of panel data. The analysis tool used is Evies 9 and Spss 16.0. This study uses a quantitative approach to secondary data with sampling technique sampling. The results of the study show that 1) Return on assets Return on equity and Net profit margin have a negative effect on Study Firm Value on state-owned banks listed on the Indonesian stock exchange. Net profit margin has a negative effect on Company Value. Indonesian stock exchange